2006
DOI: 10.1369/jhc.6a7031.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression Studies of Neogenin and Its Ligand Hemojuvelin in Mouse Tissues

Abstract: Juvenile hemochromatosis is a severe hereditary iron overload disease caused by mutations in the HJV (hemojuvelin) and HAMP (hepcidin) genes. Hepcidin is an important iron regulatory hormone, and hemojuvelin may regulate hepcidin synthesis via the multifunctional membrane receptor neogenin. We explored the expression of murine hemojuvelin and neogenin mRNAs and protein. Real-time RT-PCR analysis of 18 tissues from male and female mice was performed to examine the mRNA expression profiles. To further study prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 27 publications
2
38
0
2
Order By: Relevance
“…Neo1 is expressed in fetal premuscle masses and adult muscle Fitzgerald et al, 2006;Rodriguez et al, 2007) and, as shown here, developing somites. However, although Neo1 Gt/Gt mice displayed an obvious defect in the formation of fully sized myofibers, they did not show a defect in the formation of myotomes.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Neo1 is expressed in fetal premuscle masses and adult muscle Fitzgerald et al, 2006;Rodriguez et al, 2007) and, as shown here, developing somites. However, although Neo1 Gt/Gt mice displayed an obvious defect in the formation of fully sized myofibers, they did not show a defect in the formation of myotomes.…”
Section: Discussionsupporting
confidence: 75%
“…Defective Skeletal Muscle Development in Neo1 Gt/Gt Mice Neogenin mRNA and protein are expressed prominently in E14.5 fetal mouse muscle masses and in adult muscle Fitzgerald et al, 2006;Rodriguez et al, 2007). However, little information exists on Neo1 expression during earlier stages of myogenesis.…”
Section: The Neo1 Gt Allele Is Hypomorphic and Results In Incompletelmentioning
confidence: 99%
See 1 more Smart Citation
“…by guest www.bloodjournal.org From abundantly in liver and skeletal muscles, consistent with previous reports. 38 Intriguingly, HJV protein in neogenin mutant liver and muscle was significantly reduced (Figure 6A), suggesting a role for neogenin in HJV expression or stability. RT-PCR analysis of P20 muscle RNA demonstrated no difference at HJV mRNA levels between wild-type and mutant mice ( Figure 6B), suggesting that neogenin regulation is posttranscriptional.…”
Section: Neogenin Regulation Of Hjv Protein Level and Distributionmentioning
confidence: 94%
“…RGMc is expressed in skeletal muscle, heart, liver, bone, and cartilage (Samad et al, 2004;Niederkofler et al, 2004;Papanikolaou et al, 2004;Rodriguez et al, 2007;Kanomata et al, 2009), but its function in these tissues remains largely unknown. Nevertheless, mutations of RGMc have been linked with Hereditary Hemochromatosis, a heterogeneous group of autosomal recessive diseases that cause increased intestine absorption and deposition of iron in heart, liver, endocrine glands, joints, and skin (revised by Pietrangelo, 2007).…”
Section: Introductionmentioning
confidence: 99%